Analysis of the behavior of concrete thermomechanical of low resistance in low ages - Alexandre Jorge Rocha Menezes (2015)
Great works of infrastructure such as hydroelectric plants require, in it building, large concrete volumes classified as mass concrete structures. These works of power generation are strategic and fundamental for the development of a nation. However, during construction and throughout its life they may have pathological manifestations that compromise its stability. One of the most common problems in this type of structure is cracking caused by heat generated due to the exothermic reaction of cement hydration. Therefore, we had to analyze the thermal behavior of concrete, concrete with similar consistency and resistance like the concrete utilized in construction dam, and analyze how the type of cement utilized and its contents affects these parameters. In addition, we studied the evolution of compressive strength and dynamic modulus of elasticity as the cement hydrates. Finally, we compared the thermal performance of concretes produced with the results obtained from a commercial software. To carry out the experiment, concrete blocks were produced of 1,5mÂ with cements CP II E 32 RS and CP IV 32 with consumption 241,2 kg/mÂ and 330,0 kg/mÂ for thermal analysis, besides cylindrical specimens for the remaining analyzes. The results showed that the thermal behavior of concrete has a small dependence on the type of cement, however the cement content affects too much this behavior, and the cement CP IV 32 showed higher thermal variations. It was also observed that the development of compressive strength is strongly dependent on the cement content, but it has low dependency on the type of cement. Computer modeling presented satisfactory results when it was compared to results of the thermal evolution blocks.